Dimorfismo sexual da função quimiorreceptora a CO2/pH dos neurônios noradrenérgicos no Locus coeruleus - Dourado, Débora de Carvalho (Universidade Federal de São Carlos, 2014)
The Locus coeruleus (LC) has been suggested as a CO2 chemoreceptor site in mammals. Most of the studies involving the role of LC in hypercapnic ventilatory response have been performed in males. Since, ovarian steroids modulate the activity of LC neurons and females have a different respiratory response to CO2 of males, we evaluated the activity of LC noradrenergic neurons during normocapnia and hypercapnia in diestrus, ovariectomized (OVX; 0,2 mL/rat of corn oil, s.c., for 3 days) and estradiol-treated ovariectomized (OVX+E2; 10 μg/0,2 mL/rat, s.c., for 3 days) female rats and in intact, orchidectomized (ORX; 0,2 mL/rat of corn oil, s.c., for 7 days), testosterone-treated orchidectomized (ORX+T; 0,25 mg/0,2 mL/rat, s.c., for 7 days) and estradiol-treated orchidectomized (ORX+E2; 10 μg/0,2 mL/rat, s.c., for 3 days) male rats by using double-label immunohistochemistry to c-Fos/TH. Additionally, we assessed the role of noradrenergic LC neurons in OVX and OVX+E2 females on respiratory response to hypercapnia by using 6-hydroxydopamine. Hypercapnia (7% CO2) increased the double-staining (c-Fos/TH-ir) in LC neurons in all groups when compared to air exposure. In the OVX+E2 group there was attenuation in the c-Fos expression in normocapnia and hypercapnia. Hypercapnia increased ventilation in OVX and OVX+E2 groups, which resulted from increases of respiratory frequency (fR) and tidal volume (VT) in sham and 6-OHDA-lesioned groups. The hypercapnic ventilatory response was significantly decreased in 6-OHDA-lesioned rats compared with sham group (29.4% in OVX group and 28.7% in OVX+E2 group) due to a reduced VT in OVX+E2 group and in OVX group due to a decrease in VT and fR. A reduction in TH+ neurons (~61% in OVX and OVX+E2 group) was observed seven days after the microinjections of 6-OHDA in the LC. LC chemical lesion and estradiol did not affect body temperature (Tb). However, hypercapnia caused reduction in Tb of sham (OVX 10 and OVX+E2) and lesioned groups. Thus, we can conclude that noradrenergic neurons in the LC of female and male rats are activated by CO2. However, in OVX+E2 group, estradiol reduced the immunoreactivity compared to OVX group during normocapnia and hypercapnia. Additionally, LC noradrenergic neurons play role in hypercapnic ventilatory response in females but do not affect temperature regulation during normocapnic and hypercapnic conditions.
Keywords: Quimiorrecepção; Quimiossensibilidade; Estradiol; Hipercapnia; Ventilação pulmonar; C-Fos; Chemosensitivity; Estradiol; Hypercapnia; Ventilation; CIENCIAS BIOLOGICAS::FISIOLOGIA